2010
DOI: 10.1007/s00520-010-0997-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective longitudinal study of chemotherapy-induced cognitive changes in breast cancer patients

Abstract: These results suggest that having a breast cancer diagnosis may be associated with cognitive impairment. While chemotherapy may have a negative impact on cognitive function, chemotherapy-related impairments appear to be more acute than chronic side effects of therapy. Further studies are needed to provide insight into the clinical significance and potential mechanisms of cancer and treatment-related cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
191
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(223 citation statements)
references
References 25 publications
(52 reference statements)
18
191
2
7
Order By: Relevance
“…Prior cognitive studies have shown declines after chemotherapy, with improvement over time 3,8,9,30,31 (although see also Wefel et al 5 regarding later-onset cognitive changes and Kreukels et al 32 and Weis et al 33 regarding persistent cognitive deficits in a subgroup of individuals), and our recent finding of GMD changes followed the same pattern. 13 We therefore hypothesized that chemotherapy-related activation changes in WM circuitry would be detectable at M1 and show partial to complete recovery at Y1.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R Tsupporting
confidence: 73%
See 1 more Smart Citation
“…Prior cognitive studies have shown declines after chemotherapy, with improvement over time 3,8,9,30,31 (although see also Wefel et al 5 regarding later-onset cognitive changes and Kreukels et al 32 and Weis et al 33 regarding persistent cognitive deficits in a subgroup of individuals), and our recent finding of GMD changes followed the same pattern. 13 We therefore hypothesized that chemotherapy-related activation changes in WM circuitry would be detectable at M1 and show partial to complete recovery at Y1.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R Tsupporting
confidence: 73%
“…A growing body of evidence demonstrates that a subgroup of patients with BC have pretreatment cognitive deficits, [1][2][3][4][5] suggesting that aspects of cancer pathogenesis or host factors (potentially including variables related to BC surgery) cause cognitive changes or that there are common risk factors for the development of cancer and cognitive changes. 6 Prospective studies have shown cognitive changes differentially attributable to chemotherapy, radiation, and antiestrogen treatment, [7][8][9][10][11] highlighting the need for better understanding of potentially additive and dissociable effects of cancer treatments and the disease process on cognition in vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A significant correlation was revealed only between anxiety and performance on the Trail Making Test; however anxiety was unrelated to the other measures of cognitive functioning while depression and fatigue were not related to performance on any of the neuropsychological tests. This is also inconsistent with literature that has found that cognitive functioning declines in those with depression, anxiety and fatigue (Jansen et al, 2011).…”
Section: Emotional Functioningcontrasting
confidence: 76%
“…This is consistent with the existing literature. Jansen et al (2011) also found that those with higher levels of education and intelligence tended to perform better on neuropsychological tests and retain a higher level of cognitive functioning compared to those with lower levels of these.…”
Section: Emotional Functioningmentioning
confidence: 80%
See 1 more Smart Citation